Hemangiomas of vertebrae: treatment methods and results. - Slinko, Y. I. (Ukrainian Neurosurgical Journal)
Analyzed 83 patients during 1950 — 2001 years. The 37 patients operated (34 — open surgery, 1 — combined transvasal and open surgery, 2 — percutaneous vertebroplasty). Among open surgical intervention — 2 were transthoracic, other — utilized posterior approaches. In 2 patients intervention accomplished spinal instrumentation. In 6 patients we used vertebroplasty during open surgery. The 29 patients irradiated, 17 — following with observation or medical treatment. The one surgery resulted in cord decompression, 22 — partial removal, 5 — subtotal, 8 — total removal or hemangioma obliteration. In 14 patients we observed no neurological improvement, 18 — partial improvement, 3 complete regression neurological signs. The follow up obtained in 16 operated patients. We concluded that treatment method must have been depending from hemangiomas aggressiveness, cord compression. The long—term result depends of tumor resection radicalism.